The Effect Of Convenience, Security, And Service Features In Millenial Choices For Bsi Mobile Sub-Branch Office Nganjuk Yos Sudarso - Ayu Defani, Rena; Pipit Fitriani, Ajeng (JURNAL EKONOMI SYARIAH, 2024)
Introduction to The Problem: This research was intended because problems arose regarding the decision to use BSI Mobile in the millennial generation. BSI Mobile users partly come from the bank's obligation to register. This indicates that some BSI Sub-Branch Office Nganjuk Yos Sudarso customers still need to gain more awareness of using BSI Mobile with its convenience, security problems, service features available in line with technological development trends, and the need for efficiency in banking services.Purpose/Objective Study: This research aims to test and analyze the influence of Convenience, Security and Service Features on the Decision to Use BSI Mobile in the Millennial Generation partially and simultaneously.Design/Methodology/Approach: This research uses a quantitative approach using data. The sample used was 100 respondents using incidental sampling techniques. The data processing method uses the SPSS version 22.0 application and data analysis with testing steps including using the validity test, reliability test, classical assumption test, multiple linear regression test, t-test, f test, and coefficient of determination test (R2).Findings: The data analysis results show that Convenience, Security, and Service Features partially and simultaneously significantly influence the millennial generation's decision to use BSI Mobile Sub-Branch Office Nganjuk Yos Sudarso.Paper Type: Research Article